Optimising the REE-Zr-Nb potential of eudialyte and its alteration products in the Ilímaussaq complex, South Greenland - Borst, Anouk Margaretha; Mortensen, Henrik Friis; Finch, Adrian Anthony (2017)
Rare earth elements (REE) are critical to the development of a sustainable hi-tech economy [1].Eudialyte-bearing nepheline syenites provide promising alternatives to currently mined REE deposits in China, and techniques for their economic and environmental friendly exploitation are being developed. Europe hosts substantial eudialyte deposits within three rift-related peralkaline complexes, i.e. Ilímaussaq (Greenland), Lovozero (Russia), and Norra Kärr (Sweden) [2,3]. Despite being relatively low grade (c. 2 wt% TREO) compared to conventionally exploited REE phases, eudialyte is attractive for exploitation because of its (1) associated enrichment in other critical metals e.g. Zr, Nb and Ta; (2) high proportions of heavy relative to light REE (up to 1:1), (3) low U and Th contents, and (4) easy magnetic separation. Non peer reviewed